Prevalence of Mycoplasma genitalium and other sexually-transmitted pathogens among high-risk individuals in Greece - Chra, Paraskevi (Germs, 2018)
BACKGROUND: The aim of the present study was to determine the prevalence of Mycoplasma genitalium (MG) infection among individuals at high risk for sexually-transmitted diseases (STDs) at a major urban STD clinic in Athens, in view of the lack of data pertaining to this infection in Greece. METHODS: Urethral and cervical samples from 176 individuals consecutively attending the clinic and agreeing to participate were prospectively collected and tested for MG infection using conventional PCR and TaqMan Real-Time PCR. All individuals were also examined for alternative STD pathogens. RESULTS: A total of 161 individuals (91.5%) reported symptoms, while 15 individuals (8.5%) were asymptomatic. MG was detected in 5.7% (10/176) of the total population and in 5.6% (9/161) of those with symptoms, corresponding to 5.7% (5/87) of symptomatic men and 5.4% (4/74) of symptomatic women. Among symptomatic males, 3.4% (3/87) displayed MG mono-infection. The median age of MG infected individuals was 25 years (IQR 21.5-29.5 years). Individuals infected with MG were more likely to be coinfected with Ureaplasma spp. [OR=5.12, 95%CI, 1.27-20.57] (p=0.017). MG infection was also more common among individuals who had received antibiotics in the previous 15 days [OR=6.04, 95%CI, 1.37-26.64] (p=0.035). CONCLUSION: MG was found to represent an important microbial pathogen among patients presenting with symptoms of urethritis or cervicitis in Greece. Consideration of MG as cause of STD seems crucial in diagnostic algorithms and treatment strategies.